A Semantic Multi-Field Clinical Search for Patient Medical Records - Umamaheswari Vasanthakumar, E. (2018)
A semantic-based search engine for clinical data would be a substantial aid for hospitals to provide support for clinical practitioners. Since electronic medical records of patients contain a variety of information, there is a need to extract meaningful patterns from the Patient Medical Records (PMR). The proposed work matches patients to relevant clinical practice guidelines (CPGs) by matching their medical records with the CPGs. However in both PMR and CPG, the information pertaining to symptoms, diseases, diagnosis procedures and medicines is not structured and there is a need to pre-process and index the information in a meaningful way. In order to reduce manual effort to match to the clinical guidelines, this work automatically extracts the clinical guidelines from the PDF documents using a set of regular expression rules and indexes them with a multi-field index using Lucene. We have attempted a multi-field Lucene search and ontology-based advanced search, where the PMR is mapped to SNOMED core subset to find the important concepts. We found that the ontology-based search engine gave more meaningful results for specific queries when compared to term based search.